Characteristics and Deposit Stratigraphy of Submarine-Erupted Silicic Ash, Havre Volcano, Kermadec Arc, New Zealand - Murch, Arran P.; White, James D. L.; Carey, Rebecca J. (Frontiers in Earth Science, 2019)
In 2012 the largest wholly deep-subaqueous silicic eruption with any observational record occurred 700-1220 meters below sea level at Havre volcano, Kermadec Arc, New Zealand. Pre- and post- eruption shipboard bathymetry surveys, acquisition by autonomous underwater vehicle of metre-scale-resolution bathymetry, and sampling by remote-operated vehicle revealed 14 seafloor lavas and three major seafloor clastic deposits. Here we analyse one of these clastic deposits, an Ash with Lapilli unit, which drapes the Havre caldera, and interpret the fragmentation and dispersal processes that produced it. Seafloor images of the unit reveal multiple subunits, all ash dominated. Sampling destroyed layering in all but two samples, but by combining seafloor imagery with granulometry and componentry, we were able to determine the subunits’ stratigraphy and spatial extents throughout the study area. Five subunits are distinguished; from the base these are Subunit 1, Subunit 2a, Subunit 3, Subunit 4 (comprising the coeval Subunit 4 west and Subunit 4 east), and Subunit 2b. The stratigraphic relationships of the four Ash with Lapilli unit subunits to other seafloor products of the 2012 Havre eruption, coupled with the wealth of ROV observations and detailed AUV bathymetry, allow us to infer the overall order of events through the eruption. Ash formed by explosive fragmentation of a glassy vesicular magma and was dispersed by a buoyant thermal plume and dilute density currents from which Subunits 1 and 2 were deposited. Following a time break (days/weeks?), effusion of lava along the southern caldera rim led to additional ash generation; first by syn-extrusive ash venting, quenching, brecciation, and comminution (S3 and S4e) and then by gravitational collapse of a dome (S4w). Slow deposition of extremely fine ash sustained S2 deposition across the times of S3 and S4 emplacement, so that S2 ash was the last deposited. These thin ash deposits hold information critical for interpretation of the overall eruption, even though they are small in volume and bathymetrically unimpressive. Ash deposits formed during other submarine eruptions are similarly likely to offer new perspectives on associated lavas and coarse pumice beds, both modern and ancient.